Association between Lifestyle habits, Nutrition and Oral Cancer: A Contemporary Update - Dr Sanchit Pradhan; Dr Anupriya Srivastava; Dr Supurna Pandit; Dr Mohnish Muchhal; Dr Mayank Das (The Bioscan, 2025)
Oral cancer is a major cause of death from oral disorders worldwide and one of the worldwide major public health problems with a significant incidence and mortality rates in the developing and developed countries. Oral cancer ranks in the top three of all cancers in India, which accounts for over thirty per cent of all cancers reported in the country and oral cancer control is quickly becoming a global health priority. To reduce the burden of risk of oral cancer, a healthy diet must be optimized mainly by consuming low amount of animal-based fat red or processed red meat. Eating more quantity of vegetables, fruits and cereals are considered to be the primary origin of vitamins and fibers which is sufficient in the everyday diet to provide vitamin C, E antioxidants zinc β-carotene and folate all being an impact in the restraining of oral cancer. High consumption of healthy grains, unsaturated fats fruits and vegetables effective herbs and low use of animal-based derivatives might be the key to prevention of human cancers including the oral cancers. A public health approach should be adopted though promoting preventive measures to bring awareness among the community for taking optimum nutritive diet and practicing good lifestyle habits.